Recent Improvements of Power Plants Management and Technology - Nikolic, Aleksandar B.; Janda, Zarko S. (IntechOpen, 2017)
Since first AC current high-power hydropower plant was put in operation, built by Nikola Tesla and George Westinghouse in 1895 on Niagara Falls, electrification of the world has dramatically changed. The growing power demand and energy consumption in the last decades require fundamental changes in the process, power production, and services. These requirements tend to use both conventional and nonconventional energy generation in order to have power plants economically useful and environmentally friendly to the society. The goal of this textbook is to provide an up-to-date review of this important topic with specific emphasis on the current guidelines for improving overall efficiency, lowering emissions, and using large share of renewable energy.